Mechanical Properties of Concrete Containing 100% Recycled Homogeneous Ceramic Aggregates - Nor Hasanah, Abdul Shukor Lim; Mostafa, Samadi; Nur Farhayu, Ariffin; Mohammadhosseini, Hosein; Nur Hafizah, Abd Khalid; Abdul Rahman, Mohd. Sam (2017)
Construction industry contribute up to 70% of the wastes in the worldwide. Consequently, utilizing recycled aggregates which do not have negative effect on the properties of concrete help to reduce presser on environment and reduce depletion of natural resources. Depends on the grade, mix design and application of the concrete 65 to 85% of the concrete is consist of aggregates. In this experimental work focuses on replacing 100 % of natural aggregates by recycled fine and coarse aggregates from homogenous ceramic tile waste. Effect of this replacement on mechanical properties of concrete specimens such as compressive strength and flexural strength was investigated. The specimens were cast in 100 x 100 x 100 mm cube for compressive strength test and 100x100x500 mm size for flexural strength test. At the age of 28 days, the compressive strength of specimen containing 100% recycled aggregates was found reach to 97% of control specimen which is quite like control specimen.